Caring dan Observing Orang Tua Kepada Anak - Pertiwi, Yuarini Wahyu; Pohan, Hema Dayita; Hutahaean, Erik Saut H; Thamrin, Djuni; Perdini, Tiara Anggita (Jurnal Pengabdian kepada Masyarakat UBJ, 2021)
Abstract RPTRA is a community established by the DKI Jakarta government in order to improve the quality of life of its citizens, which in this case is specifically to support the growth and development of children, the comfort of parents and the comfort of its citizens in interacting. Children's growth and development is a mandatory thing that must be considered by parents, therefore the role of parents in providing care is important. In providing care, parents must have good care and observation of their children. If parents pay less attention and care to their children, it is feared that children will have difficulty in completing their developmental tasks. At this community service activity, the implementing team will provide material presentations about care and attention that will be conveyed through the lecture method. The results show that there are many variants of answers from the participants regarding parenting, the participants also better understand how to be parents who care and pay attention to their children. This activity still has limitations in the form of small stimuli, because the material provided is still only providing additional knowledge to parents. Follow-up activities are still needed so that parents can also apply knowledge effectively to their children. Then for the government, especially the RPTRA administrators, it is hoped that they can hold programs that can increase the bond between parents and children. Keywords: Children, Parents, Caring, Observing, Parenting Abstrak RPTRA merupakan komunitas yang didirikan oleh pemerintah DKI Jakarta guna untuk meningkatkan kualitas hidup para warganya yang dalam hal ini khusus kepada mendukung tumbuh kembang anak, kenyaman orang tua serta kenyamanan warganya dalam berinteraksi. Tumbuh kembang anak merupakan hal wajib yang harus diperhatikan oleh para orang tua, oleh karena itu peran orang tua dalam memberikan pengasuhan merupakan hal penting. Dalam memberikan pengasuhan, orang tua harus memiliki kepedulian dan pengamatan yang baik terhadap anak-anaknya. Apabila orang tua kurang memperhatikan dan peduli kepada anaknya, maka dikhawatirkan anak akan kesulitan dalam menyelesaikan tugas-tugas perkembangannya. Pada kegiatan pengabdian masyarakat kali ini tim pelaksana akan memberikan pemaparan materi mengenai kepedulian dan perhatian yang akan disampaikan melalui metode ceramah. Hasilnya menunjukan banyak varian jawaban dari para peserta kegiatan mengenai pengasuhan, para peserta pun lebih memahami bagaimana menjadi orang tua yang peduli dan memperhatikan anak. Kegiatan ini masih memiliki keterbatasan berupa rangsangan kecil, karena materi yang diberikan masih sekedar memberikan tambahan pengetahuan kepada orang tua. Kegiatan lanjutan masih diperlukan agar orang tua juga dapat mempraktekan pengetahuan secara efektif kepada anak-anaknya. Kemudian bagi pemerintah khususnya para pengurus RPTRA, diharapkan dapat mengadakan program-program yang dapat meningkatkan kelekatan orang tua dan anak. Kata kunci: Anak-Anak, Orang Tua, Kepedulian, Perhatian, Pengasuhan